Epicardial fat thickness, an emerging cardiometabolic risk factor, is increased in young adults born preterm. (3rd June 2016) - Bassareo, P. P.; Fanos, V.; Puddu, M.; Marras, S.; Mercuro, G.
Abstract : Preterm birth and epicardial fat thickness (EFT) constitute novel risk factors for the onset of future adverse cardiovascular events. In total, 30 ex-extremely low birth weight (ex-ELBW) subjects (10 males, 20 females, aged 17–28) were enrolled and compared with 30 healthy peers. EFT was significantly higher (8.7±0.7 mm v . 5.6±0.9 mm; P <0.001) in ex-ELBW than in controls and was correlated with birth weight ( r =−0.47, P =0.0009), gestational age ( r =−0.39, P =0.03) and cardiac left ventricular mass ( r =0.51, P =0.004). When excluding the influence of body mass index, birth weight was the sole remaining determinant of EFT, irrespective of gestational age ( r =−0.37, P =0.04). The same findings when excluding the possible influence of blood pressure values on the cardiac structures ( r =−0.40, P =0.028). In conclusion, EFT is significantly higher in former preterm subjects and is likewise associated with an increase in left ventricular mass. In view of the acknowledged correlation between the latter and an increased incidence of cardiovascular diseases, EFT appears to be an easy-to-measure tool capable of predicting the likely development of future adverse cardiovascular events in these subjects.